Scaling agile in large organizations: Practices, challenges, and success factors. Issue 10 (16th May 2018) - Kalenda, Martin; Hyna, Petr; Rossi, Bruno
Abstract: Context: Agile software development has nowadays reached wide adoption. However, moving agile to large‐scale contexts is a complex task with many challenges involved. Objective: In this paper, we review practices, challenges, and success factors for scaling agile both from literature and within a large software company, identifying the most critical factors. Method: We conduct a focused literature review to map the importance of scaling practices, challenges, and success factors. The outcome of this focused literature review is used to guide action research within a software company with a view to scaling agile processes. Results: Company culture, prior agile and lean experience, management support, and value unification were found to be key success factors during the action research process. Resistance to change, an overly aggressive roll‐out time frame, quality assurance concerns, and integration into preexisting nonagile business processes were found to be the critical challenges in the scaling process. Conclusion: The action research process allowed to cross‐fertilize ideas from literature to the company's context. Scaling agile within an organization does not need to follow a specific scheme, rather the process can be tailored to the needs while keeping the core values and principles of agile methodologies. Abstract : We investigate practices, challenges, and success factors for scaling agile software development. We follow a 2‐step process: a literature review used as input for an action research process within a company scaling‐up the development process. Culture within the company and prior agile and lean experience, management support, unification of views, and values were key success factors, while resistance to change, too quick roll‐out, quality assurance issues, and integration with previous non‐agile parts of the organization were critical challenges